Seek, and you shall find - Katarina Čobec (Stridon)
The Bible is the most frequently quoted text in European languages. In English, it is the King James Bible that has had the greatest cultural influence, mainly because it provided the language with hundreds of idiomatic expressions. Biblical quotations and expressions are also used in politics. The study reported in this article identifies the English biblical elements in the plenary sessions of the European Parliament (EP) from 2019 to 2024 in order to analyse their interpretation into Slovene and French. Quotations were identified by searching the EP corpus with keywords that can introduce biblical references, while biblical expressions were identified using a predefined list. Six examples of quotations and 41 different biblical expressions were identified. The accuracy and completeness of the analysed interpretations shed light on the biblical knowledge of the interpreters, who come from two countries with different cultural backgrounds but similar regulations on religious education in public schools, and both facing growing religious illiteracy. The results show that French interpreters fare slightly better than Slovene ones, and that while a satisfactory interpretation is possible without knowledge of the biblical reference, the overall quality of the message is much better when the interpreter is aware of it.